Effects of Garlic Extract (Allium sativum Linn.) Meal on Feed Efficiency and Immunity of Tropical Chickens - Utami, Merry Muspita Dyah; Pantaya, Dadik; Agus, Ali (Jurnal Sain Peternakan Indonesia, 2023)
Exploring the advantages of medicinal plants encourages research on the effectiveness of medicinal plants as a substitute for antibiotics to stimulate metabolism and immunity and improve the performance and productivity of tropical chickens. This research was conducted to determine the feed efficiency and immunity of tropical chickens fed a basal diet substituted with varying amounts of garlic extract (GE). This study utilized 150 chickens that were grouped into five treatments. Each treatment had three replicates, and each replicate consisted of 10 chickens. The treatment was GE0 = control diet, GE2 = basal diet + GE 2%, GE4 = basal diet + GE 4%, GE6 = basal diet + GE 6%, and GE8 = basal diet + GE 8%. The results showed that adding garlic extract positively affected this research, indicating that garlic extract might improve the feed efficiency and immunity of tropical chickens.